Empirical aspects of strand displacement amplification. - Walker, G T

(untitled) (Genome Research, 1993)
The most attractive feature of SDA is its operation at a single temperature, which removes the need for instrumented temperature cycling as with PCR and the ligase chain reaction. Highly reproducible temperature profiles, over a large array of samples, can burden the accuracy and expense of an amplification technique. However, the expense of a temperature cycler is offset somewhat by the cost of additional enzymes used in isothermal techniques. In comparisons with isothermal, transcription-based techniques, SDA requires fewer enzymes and has a simpler mechanism. SDA may also be more robust than transcription-based processes because it is not susceptible to contaminating ribonuclease activity. This is generally more of a concern when using clinical samples. The most significant disadvantage of SDA is its inability to efficiently amplify long target sequences. Until this short-coming is eliminated, SDA will be assigned to the diagnostic laboratory along with the ligase chain reaction. Currently, SDA cannot compete with PCR in research applications such as the isolation of gene sequences. The second disadvantage of SDA is that it operates at relatively low (nonstringent) temperatures, which produces considerable background reactions. Consequently, SDA reaction products cannot be analyzed routinely by ethidium-stained gel electrophoresis, as is used commonly with PCR, unless the target sample contains a large number of initial targets.